LAPAROSCOPIC FENESTRATION OF POLYCYSTIC LIVER DISEASE - A CASE REPORT - DR.K.V.RAJAN; DR. HARSH CHUGH (International Journal of Pharma and Bio Sciences, 2014)
Polycystic liver disease is an uncommon cystic liver disease that is transmitted through autosomal dominant inheritance. We present the case of a 65 years old female patient with massive polycystic liver disease, diagnosed by ultrasound examination and abdominal computed tomography scan. The clinical course of this disease is often complicated by compressive symptoms due to the large size of the cysts. Our patient presented with upper abdominal pain, nausea, vomiting, early satiety and discomfort during meals for 3 months. Cyst fenestration through laparoscopic approach resolved the symptoms. The patient was mobilized on the day of the surgery, and was discharged on the 3rd postoperative day, after drain tube removal. The laparoscopic approach is an established standard of care for treatment of simple hepatic cysts. The patients greatly benefit from the advantages of minimally invasive surgery.